An efficient synthesis and In vitro cytostatic activity of 5-aminosulfonyl uracil derivatives - Ismaili, Hamit (Array, 2019)
Efficient synthesis of 5-aminosulfonyl uracil derivatives 2-9 and results of their antiproliferative activity are provided. Sulfonylation of the amino group in 5-aminouracil 1 with selected arylsulfonyl chlorides occurs regioselectively when the reaction is carried out in pyridine at room temperature. Simple isolation of the products by recrystallization of the crude product mixture from aqueous methanol provides good to excellent yields. The prepared 5-aminosulfonyl uracil derivatives 2-9 were tested for the antiproliferative activity on a panel of seven tumor cell lines of different histological origin (HeLa, Caco-2, NCI-H358, Raji, HuT78, Jurkat, K562) and normal MDCK I cells. Derivatives 2-9 were found more efficient to lymphoma and leukemia cells compared to solid tumor and normal cells.